Wstępne uwagi o językowym obrazie stwórcy w Tekstach Piramid – najstarszej religijnej „księdze” świata - Popielska-Grzybowska, Joanna (Poznańskie Spotkania Językoznawcze, 2015)
The author of the paper will attempt to scrutinise, with reference to contextual arguments, a linguistic image of the Egyptian creator in the Old Kingdom religious texts which will be analysed with use of linguistic worldview method. An important inspiration for the author were the studies of Slavonic antiquity conducted by V.V. Ivanov and V.N. Toporov within the structural paradigm using the notion of opposition and the Egyptological, philosophical, anthropological and linguistic studies of J.P. Allen, J. Assman, H. Altenmüller, E. Hornung, P. Tillich, P. Wheelwright and R.A. Rappaport, and Polish scholars – T. Dobrzyńska, M. Makuchowska and the late philosopher L. Kołakowski. The paper is, however, solely an introduction to a further study. The author of the paper is making efforts to define an image of the creator expressed through and in the Egyptian language, reconstituted from fragmentary verbal messages, pictures recorded and preserved in language. It seems crucial that the Egyptian creator-god as “completed one”, comprising in himself all living beings, is embodied in his children and the whole created world.